VALUASI TERPURUK: DAMPAK PANDEMI COVID-19 TERHADAP PER DAN PBV DI 16 PERUSAHAAN LQ45 - Indah, Sayekti; Fat, Faizal Amirul (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
The corona virus pandemic that occurred at the end of 2019 had a very real and broad impact on the global economy. As social distancing policies are implemented, business closures and economic uncertainty increase, many companies are facing major challenges in maintaining their operations and preserving the value of investments. The LQ45 index is the 45 most liquid and large capitalization shares on the Indonesian Stock Exchange. This research will try to analyze the impact of the COVID 19 pandemic on the valuation of companies listed in the LQ45 Index by reviewing changes in PER and PBV values. This research uses a quantitative approach to collect and analyze data statistically. The main data source is taken from the financial reports of LQ45 index companies listed on the Indonesia Stock Exchange. The population in this research is all LQ45 Index companies on the Indonesia Stock Exchange, totaling 45 companies. The samples obtained in this research amounted to 15 companies. The data and results of this research dramatically conclude that the COVID 19 pandemic brought significant uncertainty and adjustments in the market valuation of companies in Indonesia, which was reflected in the decline in PER and PBV after 2020.